2016
DOI: 10.2320/matertrans.m2016085
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Viscosity of Particles Reinforced 7075 Al Matrix Composites

Abstract: In-situ TiB 2 particle reinforced 7075 Al alloy was produced by molten salt method (LSM). The effects of TiB 2 content on the microstructure, the melting behavior and the viscosity of 7075 Al alloy were investigated. The experimental results have shown that the microstructure became uniform rosette grains and the grain size decreased with increasing TiB 2 particles. The morphology of grains became bigger with dendritic structure when the TiB 2 particles content is more than 4.5% . The liquidus and solidus temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The liquidus and solidus temperatures of 7075 Al alloy are 635°C and 474°C respectively. The liquidus temperatures of 3.0%, 4.5% and 6.0%TiB 2 /7075 Al matrix composites are 643.1°C, 639.6°C and 644.8°C with heating speed of 5°C/min respectively, the solidus temperatures of 3.0%, 4.5% and 6.0%TiB 2 /7075 Al matrix composites are 605.3°C, 600.7°C and 597.5°C respectively [11] . The liquidus and solidus temperatures of TiB 2 /7075 Al matrix composites firstly increase then decrease with the increase of TiB 2 content.…”
Section: Effect Of Tib 2 Particles On Microstructures Of As-cast 7075...mentioning
confidence: 95%
See 1 more Smart Citation
“…The liquidus and solidus temperatures of 7075 Al alloy are 635°C and 474°C respectively. The liquidus temperatures of 3.0%, 4.5% and 6.0%TiB 2 /7075 Al matrix composites are 643.1°C, 639.6°C and 644.8°C with heating speed of 5°C/min respectively, the solidus temperatures of 3.0%, 4.5% and 6.0%TiB 2 /7075 Al matrix composites are 605.3°C, 600.7°C and 597.5°C respectively [11] . The liquidus and solidus temperatures of TiB 2 /7075 Al matrix composites firstly increase then decrease with the increase of TiB 2 content.…”
Section: Effect Of Tib 2 Particles On Microstructures Of As-cast 7075...mentioning
confidence: 95%
“…7075 Al alloys have been widely used as structural materials in aeronautical industries due to their attractive comprehensive properties, such as low density, high strength, ductility and toughness, but 7075 Al alloys had a relatively coarse dendrites which made manufacturing with semi-solid slurries difficult. Previous work has shown that SSM processing were appropriate for 7075 Al alloy by adding TiB 2 particles, including rheocasting and thixocasting [7][8][9][10][11][12] . However, the particles were easy to settle resulting in non-uniform microstructures which affected its performance.…”
Section: Introductionmentioning
confidence: 99%